Probiotic Gut Microbiota Isolate Interacts with Dendritic Cells via Glycosylated Heterotrimeric Pili. - Hanne L P Tytgat; Nienke H van Teijlingen; Ruby May A Sullan; François P Douillard; Pia Rasinkangas; Marcel Messing; Justus Reunanen; Reetta Satokari; Jos Vanderleyden; Yves F Dufrêne; Teunis B H Geijtenbeek; Willem M de Vos; et al. (PLoS ONE, 2016)
Mapping of the microbial molecules underlying microbiota-host interactions is key to understand how microbiota preserve mucosal homeostasis. A pivotal family of such bacterial molecules are pili. Pili are proteinaceous cell wall appendages with a well-documented role in adhesion, whilst their role in immune interaction with the host is less established. Gram-positive pili are often posttranslationally modified by sortase-specific cleavage reactions and the formation of intramolecular peptide bonds. Here we report glycosylation as a new level of posttranslational modification of sortase-dependent pili of a beneficial microbiota species and its role in immune modulation. We focused on the SpaCBA pili of the model probiotic and beneficial human gut microbiota isolate Lactobacillus rhamnosus GG. A unique combination of molecular techniques, nanoscale mechanical and immunological approaches led to the identification of mannose and fucose residues on the SpaCBA pili. These glycans on the pili are recognized by human dendritic cells via the C-type lectin receptor DC-SIGN, a key carbohydrate-dependent immune tailoring pattern recognition receptor. This specific lectin-sugar interaction is moreover of functional importance and modulated the cytokine response of dendritic cells. This provides insight into the direct role bacterial glycoproteins can play in the immunomodulation of the host. Modification of the complex heterotrimeric pili of a model probiotic and microbiota isolate with mannose and fucose is of importance for the functional interaction with the host immune lectin receptor DC-SIGN on human dendritic cells. Our findings shed light on the yet underappreciated role of glycoconjugates in bacteria-host interactions.